SUCCESSFUL USE OF RITUXIMAB TO TREAT GLUCOCORTICOID RESISTANT LYMPHOPLASMACYTIC HYPOPHYSITIS: A CASE REPORT - Gamage, Kavinga; Pathmanathans, Sivatharshya; Sumanatilleke, Manilka; Grossman , Ashley (Journal of the ASEAN Federation of Endocrine Societies, 2022)
BACKGROUND Lymphoplasmacytic hypophysitis is very rare and due to that its treatment is unclear. We present a case of glucocorticoid resistant lymphoplasmacytic hypophysitis successfully treated with rituximab. CASE A 34-year-old Sri Lankan male, presented with subacute onset severe headache and right sided visual impairment over 2 weeks without fever. He experienced nocturia with polydipsia since late adolescence which worsened with the onset of current symptoms. Later, he developed right sided parotitis. His height was 153 cm, BMI was 22.4 kg/ m2. There was complete vision loss in right visual field and bilateral optic nerve atrophy with more severe involvement on the right. He lacked secondary sexual characteristics. Hormonal evaluation demonstrated secondary hypothyroidism, hypoadrenalism, hypogonadism, low IGF-1, and normal prolactin levels. Osmolality studies confirmed the presence of diabetes insipidus. Brain MRI showed hypoplastic pituitary with contrast enhancing stalk, infiltration in the sellar, suprasellar and parasellar regions with optic nerve and cavernous sinus invasion. Parotid biopsy was normal. Inflammatory markers were elevated. Complete blood count was normal except for mild anemia. Tuberculosis, HIV, Aspergillosis, vasculitis, sarcoidosis and Langerhans Cell Histiocytosis were excluded. Lymphocytic hypophysitis was presumed and was started on methyl prednisolone pulses with pituitary hormone replacement. Due to poor response and progression of disease, he underwent transsphenoidal biopsy which showed lymphoplasmacytic infiltration with sclerosis suggesting possible IgG4 disease. IgG4 staining was not available. Serum IgG4 levels were normal. Intravenous rituximab pulses (1 g) were given 2 weeks apart There was marked response to rituximab. His headache settled, nasal desmopressin was tailed off and resulted in slight improvement of the vision of blind eye. Follow-up MRI scans after 5 months revealed no progression from baseline. CONCLUSION Rituximab may give promising results in the presence of glucocorticoid resistant lymphoplasmacytic hypophysitis.